2006
DOI: 10.1093/jb/mvm010
|View full text |Cite
|
Sign up to set email alerts
|

Membrane Topology of Aspartate:Alanine Antiporter AspT from Comamonas testosteroni

Abstract: We cloned the aspT gene encoding the L-aspartate:L-alanine antiporter AspTCt in Comamonas testosteroni genomic DNA. Analysis of the nucleotide sequence revealed that C. testosteroni has an asp operon containing aspT upstream of the l-aspartate 4-decarboxylase gene, and that the gene order of the asp operon of C. testosteroni is the inverse of that of Tetragenococcus halophilus. We used proteoliposomes to confirm the transport processes of AspTCt. To elucidate the two-dimensional structure of AspTCt, we analyse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…AspT is classified as a conventional secondary transport protein and belongs to the newly classified aspartate:alanine exchanger family (TC number 2.A.81) of transporters in the system developed by Saier et al (25,26). Recently, the results of a BLAST (7) search of the nucleotide sequence of the aspT gene and the amino acid sequence of the AspT protein against current nucleotide and protein data bases, respectively, suggested that the aspartate:alanine exchanger transporters are conserved in many bacterial species (8,9). Very recently, Fukui et al (10) found SucE1, an aspartate:alanine exchanger transporter from Corynebacterium glutamicum, plays a role in the export of succinate generated during fermentation.…”
mentioning
confidence: 99%
“…AspT is classified as a conventional secondary transport protein and belongs to the newly classified aspartate:alanine exchanger family (TC number 2.A.81) of transporters in the system developed by Saier et al (25,26). Recently, the results of a BLAST (7) search of the nucleotide sequence of the aspT gene and the amino acid sequence of the AspT protein against current nucleotide and protein data bases, respectively, suggested that the aspartate:alanine exchanger transporters are conserved in many bacterial species (8,9). Very recently, Fukui et al (10) found SucE1, an aspartate:alanine exchanger transporter from Corynebacterium glutamicum, plays a role in the export of succinate generated during fermentation.…”
mentioning
confidence: 99%